Effects of red ginseng oil(KGC11o) on testosterone-propionate-induced benign prostatic hyperplasia - Jeong Yoon Lee; Sohyuk Kim; Seokho Kim; Jong Han Kim; Bong Seok Bae; Gi-Bang Koo; Seung-Ho So; Jeongmin Lee; Yoo-Hyun Lee (Journal of Ginseng Research, 2022)
Background: Benign prostatic hyperplasia (BPH) is a disease characterized by abnormal proliferation of the prostate, which occurs frequently in middle-aged men. In this study, we report the effect of red ginseng oil (KGC11o) on BPH. Methods: The BPH-induced Sprague-Dawley rats were divided into seven groups: control, BPH, KGC11o 25, 50, 100, 200, and finasteride groups. KGC11o and finasteride were administered for 8 weeks. The BPH biomarkers, DHT, 5AR1, and 5AR2, androgen receptor, prostate-specific antigen (PSA), Bax, Bcl-2, and TGF-β were determined in the serum and prostate tissue. The cell viability after KGC11o treatment was determined using BPH-1 cells, and, androgen receptor, Bax, Bcl-2, and TGF-β were confirmed by western blotting. Results: In the in vivo study, administration of KGC11o reduced prostate weight by 18%, suppressed DHT (up to 22%) and 5AR2 (up to 12%) levels from administration of 100 mg/kg KGC11o (P < 0.05). PSA was significantly downregulated dose-dependently from at the concentration of 50 mg/kg KGC11o (P < 0.05). BPH-1 cell viability significantly reduced through the treatment with KGC11o. In vitro and vivo, AR, Bcl-2 TGF-β levels reduced significantly but Bax was increased (P < 0.05). Conclusion: These results suggest that KGC11o may inhibit the development of BPH by significantly reducing the levels of BPH biomarkers via 5ARI, anti-androgenic effect, and anti-proliferation effect, serving as a potential functional food for treating BPH.